Expression of the cloned gene for enterotoxin STb of Escherichia coli. - Lawrence, R M (1990)
This study involved the construction of hybrid plasmids to produce heat-stable enterotoxin type II of Escherichia coli (STb). The translation of the open reading frame for the STb gene estA was demonstrated in several ways. Studies using in vivo labeling with [35S]cysteine demonstrated a radiolabeled protein band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the expected molecular weight of 5,000 for toxin STb. Insertion of translational or transcriptional termination signals into the BglII site of the estA gene blocked the expression of estA. The estA gene was cloned into high-expression vector pKC30 downstream from the strong pL promoter. Northern (RNA) blotting assays revealed a 10- to 20-fold increase in mRNA produced by strain C600F(pKC30STb) over other STb-producing strains, compared with little or no increase in enterotoxin activity demonstrated by bioassay. The estA gene, with its own promoter and Shine-Delgarno region and a portion of the sequence for the signal peptide deleted, was also inserted under the control of the tac promoter. Even after induction of the tac promoter by addition of isopropyl-beta-D-thiogalactopyranoside, no biologic enterotoxin activity could be identified. Neutralizing antibodies to STb were produced in rabbits by using either a purified OmpF-STb-beta-galactosidase fusion protein or a 19-amino-acid synthetic STb peptide coupled to keyhole limpet hemocyanin.